The interleukin-6 –174 G/C promoter polymorphism and arterial stiffness; the Rotterdam Study - Mark PS Sie; Francesco US Mattace-Raso; André G Uitterlinden; Pascal P Arp; Albert Hofman; et al (Vascular Health and Risk Management, 2008)
Mark PS Sie1, Francesco US Mattace-Raso2, André G Uitterlinden2, Pascal P Arp2, Albert Hofman1, Huibert AP Pols2, Arnold PG Hoeks3, Robert S Reneman4, Roland Asmar5, Cornelia M van Duijn1, Jacqueline CM Witteman11Department of Epidemiology and Biostatistics, 2Department of Internal Medicine, Erasmus Medical Center, Rotterdam, The Netherlands; 3Department of Biophysics, 4Department of Physiology, Cardiovascular Research Institute Maastricht, Maastricht University, Maastricht, The Netherlands; 5Cardiovascular Institute, Paris, FranceAbstract: Arterial stiffness normally increases with age and has been established as a precursor of cardiovascular disease. Interleukin-6 is a pleiotropic inflammatory cytokine with an important role in the inflammatory cascade, such as up-regulation of C-reactive protein (CRP). The interleukin-6 –174-G/C promoter polymorphism appears to infl uence levels of inflammatory markers, which have been shown to be associated with arterial stiffness. We studied the association of this polymorphism with levels of interleukin-6 and CRP and with arterial stiffness. The study (n = 3849) was embedded in the Rotterdam Study, a prospective, population-based study. Analyses on the association between the –174-G/C polymorphism and pulse wave velocity, distensibility coefficient, and pulse pressure were performed using analyses of variance. Analyses on the levels of inflammatory markers and arterial stiffness were performed using linear regression analyses. Analyses were adjusted for age, sex, mean arterial pressure, heart rate, known cardiovascular risk factors, and atherosclerosis. We found pulse wave velocity to be 0.35 m/s higher for CC-homozygotes vs. wildtype GG-homozygotes (p = 0.018) with evidence for an allele-dose effect (p trend = 0.013), and a similar pattern for pulse pressure (p trend = 0.041). No apparent consistent association with the distensibility coefficient was found. CRP levels were associated with pulse wave velocity (p = 0.007). In conclusion, the interleukin-6 –174 G/C polymorphism is associated with increased arterial stiffness and pulse pressure.Keywords: IL-6, CRP, arterial stiffness, pulse wave velocity, distensibility coefficient, pulse pressure